2021
DOI: 10.1080/03323315.2021.1916555
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: teaching primary geography in an authentic context related to the lived experiences of learners

Abstract: The Covid-19 pandemic is an unanticipated event that has exposed human fragility in an interconnected and interdependent world. While impacts are of a global magnitude, they have been felt at the most local of levels. Across the world pupils' daily lives and experiences have been directly impacted by government-imposed measures and restrictions taken to address the pandemic. Existing research on the teaching of primary geography in Ireland, although both dated and limited, indicates the prevalence of didactic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Although COVID-19 is a recent phenomenon and is not yet part of the Omani social studies curriculum, the participants viewed the topic as an important event and they stressed several examples of integrating it into their instruction. This view is consistent with the argument that COVID-19 offers rich opportunities for meaningful teaching and learning in social studies and geography education (Kidman & Chang, 2020;Usher & Dolan, 2021;van der Schee, 2020). In line with this finding, the participants stressed the importance of social studies in Omani schools as a vehicle to teach about various aspects of the pandemic along with other rationales-teaching important knowledge, skills, and values associated with the subject.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although COVID-19 is a recent phenomenon and is not yet part of the Omani social studies curriculum, the participants viewed the topic as an important event and they stressed several examples of integrating it into their instruction. This view is consistent with the argument that COVID-19 offers rich opportunities for meaningful teaching and learning in social studies and geography education (Kidman & Chang, 2020;Usher & Dolan, 2021;van der Schee, 2020). In line with this finding, the participants stressed the importance of social studies in Omani schools as a vehicle to teach about various aspects of the pandemic along with other rationales-teaching important knowledge, skills, and values associated with the subject.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, social studies educators can discuss the pedagogical implications of the COVID-19 pandemic in the context of a wide range of content and instructional practices (Kidman & Chang, 2020;Usher & Dolan, 2021;van der Schee, 2020). For example, addressing the COVID-19 pandemic through geography provides teachers with opportunities to connect geography to the real world and everyday experiences and encourages the use of a wide range of student-centered strategies (Usher & Dolan, 2021). In civic education, Akbulut et al (2020) reported several examples of the roles of social media during the pandemic in increasing student participation in national festivals such as National Day and Children Day.…”
Section: Opportunitiesmentioning
confidence: 99%